Iceland : Selected Issues Paper. (IMF Staff Country Reports; Country Report, 2010)
In this study, during 2008, the financial crisis lead Iceland's public debt to soar from under 30 percent of GDP to more than 100 percent of GDP, and while underlying external debt came down sharply, it remains elevated at close to 300 percent of GDP. First, external sustainability is overviewed, and second, growth of Iceland's economy has been challenged, and finally, fiscal adjustments and its macroeconomic impacts are overviewed. Traditional external debt sustainability analysis (DSA) suggests that Iceland's external debt is sustainable but is vulnerable to depreciation shock.